Imaging and printing in plastic and reconstructive surgery part 2: emerging techniques - Michael P Chae; David J Hunter-Smith; Warren M Rozen (Australasian Journal of Plastic Surgery)
**Background**: In the second of a two-part series, we evaluate emerging three-dimensional (3D) imaging and printing techniques based on computed tomography angiography (CT) and magnetic resonance angiography (MRA) for use in plastic and reconstructive surgery. **Method**: A review of the published English literature dating from 1950 to 2017 was taken using databases such as PubMed, MEDLINE®, Web of Science and EMBASE. **Results**: Image-guided navigation systems using fiducial markers have demonstrated utility in numerous surgical disciplines, including perforator-based flap surgery. However, these systems have largely been superseded by augmented reality (AR) and virtual reality (VR) technologies with superior convenience and speed. With the added benefit of tactile feedback, holograms also appear promising but have yet to be developed beyond the prototypic stage. Aided by a growing volume of digitalised clinical data, machine learning (ML) poses significant benefits for future image-based decision-making processes. **Conclusion**: Most studies of image-guided navigation systems, AR, VR, holograms and ML have been presented in small case series and they remain to be analysed using outcomes-based validation studies. However, together they illustrate an exciting future where clinicians will be armed with intuitive technologies for surgical planning and guidance.